2002
DOI: 10.1021/ed079p264
|View full text |Cite
|
Sign up to set email alerts
|

The Michael Reaction

Abstract: A brief account of the Michael reaction is provided, illustrating its versatility as a topic in undergraduate chemistry courses. Included is a short biography of the reaction's namesake, examples of its use in organic synthesis, and its unique role in the defense mechanism of the bacterium Micromonospora echinospora. A computational rationale for the selectivity of 1,4 versus 1,2 addition of nucleophiles to α,β-unsaturated carbonyls is discussed and links to animations suitable for an introductory organic chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 7 publications
(7 reference statements)
0
21
0
Order By: Relevance
“…This work is an attempt to provide such a view by taking a series of α‐substituted methyl acrylates (X=F, Cl, Me, H, CN, NO 2 ) as model Michael acceptors and methanethiol as a model Michael donor (see the red box in Figure ). These compounds were chosen because methanethiol, a soft nucleophile that favors attack at the β‐carbon atom, is an excellent model for SH reactivity in cysteine‐containing enzymes (Figure ) and because methyl acrylate has the same Michael reactive site as several drugs used to fight cancer (in particular, the structures of fluorouracil and vernolepin are shown in Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…This work is an attempt to provide such a view by taking a series of α‐substituted methyl acrylates (X=F, Cl, Me, H, CN, NO 2 ) as model Michael acceptors and methanethiol as a model Michael donor (see the red box in Figure ). These compounds were chosen because methanethiol, a soft nucleophile that favors attack at the β‐carbon atom, is an excellent model for SH reactivity in cysteine‐containing enzymes (Figure ) and because methyl acrylate has the same Michael reactive site as several drugs used to fight cancer (in particular, the structures of fluorouracil and vernolepin are shown in Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the local HSAB principle, the β-position and the carbonyl carbon atom will react with soft and less soft nucleophiles respectively. In a fashion analogous to the 1,4-Michael addition of nucleophiles to α,β-unsaturated electrophiles [13,18,19], as observed experimentally [6], the slightly soft nucleophile aniline (hardness η = 4.4 eV) [23] attacks the carbonyl carbon atom to yield 5a.…”
Section: Resultsmentioning
confidence: 90%
“…It establishes that although the softest atom in molecule A is in general the most reactive site, there may be other less soft sites, which may become the most reactive sites, regulated by the softness of the reacting molecule B [8,9]. The local HSAB principle has been widely used in studies on multiple reaction sites and in strong and weak chemical interactions [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Important in the understanding of the potential toxicity of these compound, acrylamide or derivatives is an α, ß‐unsaturated carbonyl with electrophilic reactivity that can interact with nucleophiles by the Michael addition (Poon, Mundy, & Shattuck, ). Because acrylamide‐based monomers are an electrophile, they could potentially interact with biological nucleophilic groups of amines, carboxylates, aryl, and alkyl hydroxyls, imidazoles, and thiols (Shipp et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of AAm in foods has caused worldwide concern because epidemiological and experimental studies have indicated that AAm poses a variety of health hazards including neurotoxicity, developmental toxicity, genotoxicity, reproductive toxicity, and carcinogenicity (Cooperstein & Canavan, 2013;Chou et al, 2013;Komoike & Matsuoka, 2016;Rietjens et al, 2018;Tanii, Miki, Hayashi, & Hashimoto, 1988). Important in the understanding of the potential toxicity of these compound, acrylamide or derivatives is an α, ß-unsaturated carbonyl with electrophilic reactivity that can interact with nucleophiles by the Michael addition (Poon, Mundy, & Shattuck, 2002). Because acrylamide-based monomers are an electrophile, they could potentially interact with biological nucleophilic groups of amines, carboxylates, aryl, and alkyl hydroxyls, imidazoles, and thiols (Shipp et al, 2006).…”
mentioning
confidence: 99%